“aaaaaaaaaaaaaaaaaaaaaaaaaambition makes you look [pretty] ugly”: Mass consumption and computer-generated art in Radiohead’s OK Computer - François Hugonnier (Revue LISA)
OK Computer triggers a major shift in Radiohead’s career. It questions the conditions of its making by subverting representative frames. It uses paradox in order to assimilate the mass-consumption and technological progress it both abhors and embodies. In an urban landscape of sedated “consumer-robots”, the band embraces the digital era and fuses pop-rock songs with electronic distortion. A man-machine relationship is developed as a socio-political metaphor and a straightforward report, including the use of computers in the crafting of their art. In spite of its ironic playfulness, OK Computer will not escape the commercial and technological mutations it scrutinizes: it is therefore acknowledging, in a performative way, the computer’s win over the band’s scope and music. OK Computer being thoroughly transmedia, all the elements (musical, linguistic and visual) surrounding its 1997 release are taken into account in this article, which analyses the paradox of mass-consumption denunciation, engages in cryptic decoding, and envisions this record as the first step in the band’s innovative adjustments to new technologies, be they musical or commercial.